A tribute to Almarhum Dr. Adil Khan Afridi (in IIUM-Today) - Abdul Razak, Mohd Abbas (Department of Communication, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2021)
In the morning of 12th October, 2020, I heard the sad news that Dr. Adil had passed away in Pakistan. Realizing that he has departed from this world, my natural feeling made tears to well up in my eyes. I immediately started to pray for his blessed soul to be placed among those nearest to Allah (Solihin). After that, for a day or two my mind was occupied thinking about the good times I had with this towering scholar from Pakistan. My friendship with Dr. Adil goes back to 2011 when we reported for our teaching job on the same day at the Department of Fundamental & Inter-Disciplinary studies at KIRKHS, IIUM. Ever since our first meeting, our friendship started to blossom into something more. We started addressing one another as ‘brother’. As members of the faculty, we worked together in the various committees we were involved in. Both of us worked together in a few research projects and attended many conferences. As a Muslim scholar, Dr. Adil was an expert in matters related to the Qur’an and Sunnah. He was a shining example to many of us in the department. Dr. Adil was a man of positive thinking and always looked at the brighter side of life. Being clean and tidy is part of his personality. A visit to his office enables one to smell good perfume as a form of aroma therapy that changes one’s mood, good aromatic coffee and a discussion that uplifts one’s spirituality. As a host, he had always provided the best hospitality for all those who visited his office and house. As a generous man, it was his culture to sponsor food during departmental meetings. To his students, Dr. Adil had a fatherly affection towards them. He always without fail made it an obligation on him that his students are reminded about the Prophet’s way of life. Though he was a well-established Muslim scholar, he loved to consult others for opinions on matters related to his academic and personal matters. In 2018, Dr. Adil left IIUM to take over his late father’s position in Pakistan who died of natural causes. In his homeland, Dr. Adil was given the responsibility to be the Rector of Jamia Farooqia Karachi. His last visit to Malaysia was in January, 2020. His visit was to initiate some sort of cooperation between his learning institution and IIUM. As a visionary leader and scholar, he was interested in making IIUM as a model for his own institution in terms of its research method, curriculum development and integration of knowledge. In his opinion, he viewed IIUM as the best university in the Muslim world that champions education and knowledge towards sustainable development, moderation and humanizing education towards a better world for humanity and world peace. Since Dr. Adil is no longer with us at the moment, I hope his spirit, good qualities and aspirations for the Muslim Ummah and humanity at large will live on and come to fruition.